2019
DOI: 10.1515/dmpt-2018-0040
|View full text |Cite
|
Sign up to set email alerts
|

The effect of curcumin with piperine supplementation on pro-oxidant and antioxidant balance in patients with non-alcoholic fatty liver disease: a randomized, double-blind, placebo-controlled trial

Abstract: Background The main causes of the progression of non-alcoholic fatty liver disease (NAFLD) are enhanced levels of reactive oxygen species and lipid peroxidation products. Therefore, the usage of antioxidant agents for the prevention and remedy of this disorder was recommended. Curcumin is proposed to treat NAFLD due to its high antioxidative activity. The aim of this study was to examine the effect of curcumin with piperine supplementation on oxidative stress in subjects with NAFLD. Methods In this double-bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Also, an in- vivo study has shown that curcumin is able to decrease 8-oxodGaccumulation as well as inducing the expression of oxidant-generating genes (such as COX-2 ), malondialdehyde, and plasma nitrate [ 54 ]. Moreover, curcumin has been successfully used in different trials as an antioxidant agent for diseases such as non-alcoholic fatty liver disease [ 55 ], metabolic syndrome [ 56 ], tropical pancreatitis [ 57 ], and many other diseases [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, an in- vivo study has shown that curcumin is able to decrease 8-oxodGaccumulation as well as inducing the expression of oxidant-generating genes (such as COX-2 ), malondialdehyde, and plasma nitrate [ 54 ]. Moreover, curcumin has been successfully used in different trials as an antioxidant agent for diseases such as non-alcoholic fatty liver disease [ 55 ], metabolic syndrome [ 56 ], tropical pancreatitis [ 57 ], and many other diseases [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also, the LPDHD group exhibited no significant difference in birth weight compared to the NPD group. Also, serum cortisone levels were significantly lower in the LPDHD and LPLD groups compared to the LPDs (no significant differences were observed with the NPD group).Moreover, they clearly demonstrated the antioxidant activity and ROS scavenger potential of curcumin induced by Nrf2, catalase (CTA), and heme oxygenase-1 (HO-1)expression, as well as a decrease in MDA content [53].Also, an in-vivo study has shown that curcumin is able to decrease 8-oxodGaccumulation as well as inducing the expression of oxidant-generating genes(such as COX-2), malondialdehyde, and plasma nitrate [54].Moreover, curcumin has been successfully used in different trials as an antioxidant agent for diseases such as non-alcoholic J o u r n a l P r e -p r o o f fatty liver disease [55], metabolic syndrome [56], tropical pancreatitis [57], and many other diseases [50].…”
Section: 2curcumin Inflammation and Iugrmentioning
confidence: 99%
“…586 Mirhafez et al showed that oral administration of phytosomal curcumin (500 mg/day) with piperine (5 mg/day) for 8 weeks reduced the PAB levels in patients with NAFLD (n = 24) compared to placebo controls (n = 23). 587 The same group also showed that oral administration of phytosomal curcumin (250 mg/day) for 8 weeks remarkably decreased leptin levels and increased adiponectin and HDL in patients with NAFLD (n = 33) compared to placebo controls (n = 32). 588 In another study, Saadati et al demonstrated that supplementation with 500 mg of curcumin (n = 25) 3 times a day remarkably reduced hepatic fibrosis and NF-κB in patients with NAFLD compared to placebo (n = 25).…”
Section: Turmeric and Curcumin In Inheritedmentioning
confidence: 90%
“…However, attempts to demonstrate the effect of isolated antioxidant molecules following oral intake on antioxidant status, lipid peroxidation, and inflammatory markers in humans have failed, perhaps due to the chemical instability of these molecules along the gastrointestinal trait alongside their low bioavailability in biological fluids [ 162 , 163 , 164 , 165 ].…”
Section: Critical Analysis Of the Effectiveness Of Nano-encapsulated Polyphenols On Cardiovascular Performance: Pre-clinical And Clinicalmentioning
confidence: 99%